2018
DOI: 10.3238/arztebl.2018.0437
|View full text |Cite
|
Sign up to set email alerts
|

Video Versus Direct Laryngoscopy for Inpatient Emergency Intubation in Adults

Abstract: The routine use of VL for airway management in emergency medicine might improve patient safety, as VL is associated with a lower number of intubation attempts and with a lower frequency of esophageal intubation. Further randomized controlled trials are needed before any definitive conclusions can be drawn about the advantages of video laryngoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
(42 reference statements)
0
9
0
1
Order By: Relevance
“…We excluded four meta-analyses involving the Miller blade from our systematic review. 11 , 15 , 19 , 21 Of note, three of these four were pediatric studies, 11 , 15 , 19 highlighting the heterogeneity related to Macintosh and Miller blades in the pediatric airway literature. As a straight blade, Miller blade DL is generally different from the Mac-DL technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded four meta-analyses involving the Miller blade from our systematic review. 11 , 15 , 19 , 21 Of note, three of these four were pediatric studies, 11 , 15 , 19 highlighting the heterogeneity related to Macintosh and Miller blades in the pediatric airway literature. As a straight blade, Miller blade DL is generally different from the Mac-DL technique.…”
Section: Discussionmentioning
confidence: 99%
“…Literature comparing VL to Mac-DL often describes an improved glottic view, 7 - 16 and either the same or improved tracheal intubation success with VL. 7 - 12 , 14 , 16 - 29 Additionally, several studies describe fewer complications with VL, including fewer esophageal intubations 14 , 21 , 26 , 30 and glottic trauma. 12 , 20 , 27 …”
mentioning
confidence: 99%
“…Several studies have demonstrated a higher success rate for novices with fewer complications for VL compared with DL, particularly outside of the OR [ [70] , [71] , [72] , [73] , [74] ]. This finding, however, is not consistent between studies and may be affected by the device, environment, and operator factors [ [75] , [76] , [77] ]. Additionally, it also has been suggested that novice trainees may have more rapid acquisition of DL skills when VL is practiced first with video-assisted instruction [ 78 , 79 ], although, again, this is not a consistent observation [ 80 ].…”
Section: Do You Need To Teach Direct Laryngoscopy Video Laryngoscopymentioning
confidence: 79%
“…Excessive emphasis on DL or VL using hyperangulated blades may not provide the best support for future clinical responsibilities. From a clinical perspective, the use of VL is linked to a higher success rate in this population with fewer esophageal intubations [ 77 ].…”
Section: Do You Need To Teach Direct Laryngoscopy Video Laryngoscopymentioning
confidence: 99%
“…However, a randomised trial in intensive care units (ICUs) showed no difference in first-pass intubation success rates between VLs and the Macintosh system 11. A systematic review of emergency TIs in emergency departments (EDs) and ICUs showed that the use of VLs had no significant advantage with regard to first-attempt success rates, although their use was significantly associated with a lower number of intubation attempts 12. However, these studies included various types of VL in a single group and did not consider the characteristics of each VL.…”
Section: Introductionmentioning
confidence: 99%